A Novel Buckle‐Free Large Rib Microdisk with Submicrometer Thickness. Issue 11 (8th September 2022) - Honari, Shahin; Farajollahi, Saeed; Lu, Tao
Abstract : Thin large microdisks, that are key to dense spectral microcomb generation at visible‐to‐UV wavelengths, face challenges in fabrication. One of the most difficult issues is the buckling effect that makes comb generation infeasible due to the severe degradation of cavity optical quality factor. Herein, a novel rib disk structure that significantly mitigates the buckling effects is introduced. Using this approach, millimeter‐sized buckle‐free microdisks with sub‐micrometer thickness and high optical quality factor exceeding 10 7 are obtained. Abstract : Large thin microdisks can reach anomalous dispersion for dense microcomb generation at short wavelength. However, the fabrication of such microdisks remains challenging due to buckling. Herein, a novel buckling‐free rib disk with a diameter of 1 mm and thickness below 1 μm is demonstrated. The proposed structure enables microcomb‐based in vitro single‐molecule precision spectroscopy in liquid.